Capacity Building for Adolescent Health Cadres Regarding Adolescent Reproductive Health at The Tawangrejo Health Center Madiun City - Maria Oktaviani; Agung Suharto; Astin Nur Hanifah; Heru Santosa Wahito Nugroho (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2023)
Adolescence is a phase of development between childhood and adulthood, lasting between the ages of 12-21 years. Some of the problems faced by adolescent are closely related to reproductive health. Data at the Tawangrejo Health Center for adolescent pregnancy in 2020 were 6 cases, in 2021 were 6 cases, and the first semester of 2022 were 4 cases. The purpose of the study was to determine the increased capacity of adolescent reproductive health pocket book training. The type of research is pre experiment One Group Pre Test - Post Test. The results showed a relationship between the provision of training on adolescent reproductive helath pocket book with increased capacity of adolescent health cadres. The conclusion of this study is that adolescent reproductive health pocket book training is very effective to increase the capacity of adolescent health cadres on adolescent reproductive health.